Covid-19 and its impact on venture pitching competitions in higher education: a case study. Issue 3 (2nd September 2021) - Smith, Douglass; Muldoon, Jeffrey
ABSTRACT: For the last several years, many institutions of higher learning annually have conducted venture pitch competitions. The competition allows students to experience a taste of entrepreneurship. Quite often, these competitions are performed in parallel with entrepreneurship courses. During the spring of 2020, as the COVID-19 pandemic threat became evident, higher education, much like the rest of society, had to make hard choices and adapt to a threat that wasn't fully realized at the time. This case introduces the venture pitch at one such institution, known as the Entrepreneurial Challenge (EC). The case further discusses the impact of COVID-19, and the changes, lessons learned, and suggested best practices of the EC.